Development of a bat (loban) and baseball (serpa) as media to attract students' interest in playing baseball for class IV MI Nurul Huda Gandusari - Dwiani Agustina; Vega Mareta Sceisarriya (PHEDHERAL, 2022)
The background of this research is the lack of interest of students in playing baseball because of the limitations of teachers in making innovative learning models such as making interesting media for learning to play baseball, thus making students not excited and bored with baseball material. Therefore, it is necessary to develop learning media for hitting tools (loban) and baseball (serpa) so that students are happy and interested in playing baseball. This research using the ADDIE model. The instrument in this study used questionnaires. Based on the research, it was found that with the development of learning media in the form of a punch (loban) and baseball (serpa) able to attract the interest of fourth grade students at MI Nurul Huda Gandusari it can be said that by modifying the media in the form of a punch (loban) and baseball (serpa). This can be proven from the results of the percentage value which shows the average value in the small group trial results the average value is 83% while the average value in the large group trial results shows an increase in the number of scores. the average is 93%. Thus, the development of learning media in the form of a punch (loban) and baseball (serpa) is in good category and can be used as a medium that attracts students to play baseball. Overall, the loban bat and the serpa ball were declared suitable for use in the baseball game after going through validation from media experts and traditional game experts.